Pengaruh Produk Domestik Regional Bruto (PDRB) dan Tingkat Inflasi Terhadap Jumlah Deposito Berjangka Pada Bank Umum di Provinsi Bali Periode 2014-2019 - Ni Luh Made Sri Padmi; A. A. Sri Purnami; Ita Silvia Azita Azis (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2022)
This research is entitled The Effect of Gross Regional Domestic Product (PDRB) and Inflation Rate on Time Deposits at Commercial Banks in Bali Province for the 2014-2019 Period. using secondary data obtained from reports from Bank Indonesia and the Central Bureau of Statistics of Bali Province. The processed data is time series data on a quarterly basis. In order to know the effect of GRDP, Inflation Rate on Total Time Deposits, either simultaneously or partially, is the aim of this research. Multiple linear regression is the analytical technique used. Commercial banks in Bali Province are the objects of research. The test of the F test shows that the GRDP and the Inflation Rate together (simultaneously) have a significant effect on the Total Time Deposit. The test of the t test results on the PDRB variable has a positive and significant effect on the number of time deposits at Commercial Banks in Bali Province, the inflation rate variable has a negative and significant effect on the number of time deposits at Commercial Banks in Bali Province.